Unmasking the enigma - recurrent odontogenic keratocyst: a continual challenge - Dua, Piyush; Ghosh, Shayan; Khalid, Sania; Grover, Muskan; Jaiswal, Rishabh; Gupta, Amit (International Surgery Journal, 2024)
Odontogenic keratocysts (OKCs) represent 10% to 14% of all jaw cysts and are notable for their high recurrence rate compared to other odontogenic cysts. This case study details a recurrent OKC in a young woman, highlighting the critical need for diligent long-term follow-up and effective management strategies. A 25-year-old female presented with a recurrent OKC in the maxilla. The treatment involved surgical enucleation of the cyst, apicectomy of affected teeth, and application of Carnoy's solution to reduce recurrence risk. Follow-up imaging and clinical evaluations were conducted periodically to monitor healing and detect potential recurrences. Postoperative recovery was uneventful, with no immediate complications. Serial radiographs and clinical examinations during the follow-up period showed satisfactory healing and no signs of recurrence. The patient reported no discomfort or functional impairment. This case underscores the importance of comprehensive surgical intervention and long-term follow-up in managing recurrent OKCs. The combined approach of cyst enucleation, apicectomy, and Carnoy's solution application proved effective in preventing recurrence in this patient. Ongoing monitoring remains essential to ensure early detection and management of potential recurrences, ultimately improving patient outcomes.